The ADNI PET Core: 2015 - Jagust, William J. (Alzheimers Dement, 2015)
INTRODUCTION: This paper reviews the work done in the ADNI PET core over the past 5 years, largely concerning techniques, methods, and results related to amyloid imaging in ADNI. METHODS: The PET Core has utilized [(18)F]florbetapir routinely on ADNI participants, with over 1600 scans available for download. Four different laboratories are involved in data analysis, and have examined factors such as longitudinal florbetapir analysis, use of FDG-PET in clinical trials, and relationships between different biomarkers and cognition. RESULTS: Converging evidence from the PET Core has indicated that cross-sectional and longitudinal florbetapir analyses require different reference regions. Studies have also examined the relationship between florbetapir data obtained immediately after injection, which reflects perfusion, and FDG-PET results. Finally, standardization has included the translation of florbetapir PET data to a centiloid scale. CONCLUSION: The PET Core has demonstrated a variety of methods for standardization of biomarkers such as florbetapir PET in a multicenter setting.